2006
DOI: 10.1016/j.patrec.2005.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Hausdorff distances and dynamic clustering of symbolic interval data

Abstract: This paper presents a partitional dynamic clustering method for interval data based on adaptive Hausdorff distances. Dynamic clustering algorithms are iterative two-step relocation algorithms involving the construction of the clusters at each iteration and the identification of a suitable representation or prototype (means, axes, probability laws, groups of elements, etc.) for each cluster by locally optimizing an adequacy criterion that measures the fitting between the clusters and their corresponding represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(73 citation statements)
references
References 16 publications
0
72
0
1
Order By: Relevance
“…The HD has been widely used in image matching and shape comparison tasks and can be applied to measure the similarity between two patterns of points in images denoting edges [38][39][40]. Given two finite point sets = {a1, a2, a3... am} and = {b1, b2, b3... bn}, the HD is defined as follows: …”
Section: Eddy Trackingmentioning
confidence: 99%
“…The HD has been widely used in image matching and shape comparison tasks and can be applied to measure the similarity between two patterns of points in images denoting edges [38][39][40]. Given two finite point sets = {a1, a2, a3... am} and = {b1, b2, b3... bn}, the HD is defined as follows: …”
Section: Eddy Trackingmentioning
confidence: 99%
“…Table 2 shows part of the corresponding data matrix (De Carvalho et al, 2006b); the complete data matrix is available in the SODAS (Symbolic Official Data Analysis System) Software. According to De Carvalho et al (2006b), several studies carried out in French Guyana indicated abnormal levels of mercury contamination in some Amerindian populations. This contamination was connected to their consumption of contaminated freshwater fish.…”
Section: Case Study: Freshwater Fish Data Set (Ecotoxicology Data Set)mentioning
confidence: 99%
“…In order to study this phenomenon, the data set mentioned above was collected by researchers from The symbolic objects (species) were grouped into four a priori clusters according to diet. The a priori classification is as follows (De Carvalho et al, 2006b): In order to apply the affinity coefficient a WW (k,k), with equal weights ( j =1/p), a transformed data matrix was computed, according to that described in Bacelar- Nicolau et al (2009Nicolau et al ( , 2010. Each interval variable (generalized column) gave a sub-table with a suitable number of columns corresponding to a set of elementary intervals.…”
Section: Case Study: Freshwater Fish Data Set (Ecotoxicology Data Set)mentioning
confidence: 99%
See 1 more Smart Citation
“…For considering the cluster validity problem on symbolic data, we will set up an XB-like validity index for symbolic data under the FSCM along with the XB validity index proposed by Xie and Beni [47] in Section 5. We finally mention that, because symbolic interval data (or only called interval data) are most appeared in real applications, there are various methods for clustering interval data in the literature, such as Chavent et al [6], de Carvalho et al [11,12,[14][15][16][17], de Souza et al [18], Guru et al [25,26] and Irpino and Verde [31], etc. We next propose the S-SOM for symbolic data.…”
Section: Symbolic Data With Its Dissimilarity Measuresmentioning
confidence: 99%